Extraction and Geo-Referencing Suburban Locations of Terroristic Attacks from Textual Data of Maiduguri Insurgency - Garba, S. S. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
There are no precise